Using quality tools to identify cost saving opportunities in hand layup process - Muhammad Sajarul Elyas Samsuddin (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The hand layup process is used for producing the composite sandwich panels by laying different composite materials on and bottom of the core to make a sandwich structure of the panel. Vacuum bagging process is one of the process involved in completing layup process. This process is important in order to ensure no air trapped between the plies, allow plies to be drawn together perfectly by creating secure bond between them. In this process, perforated release film is also used to accomplish the vacuum bagging process. It plays the role to act as a contact material to avoid the contact occur between the breather and the matrix resin during compaction and autoclave processes. Non-perforated release film among the high cost material that used frequently for every layup process.